Mosque Economics: A Meta-Analysis - Aisyah As-Salafiyah (Journal of Islamic Economics Literatures, 2020)
This study attempts to do a literature evaluation on the economics of mosques published in reputable journals. It uses descriptive statistics to analyze 179 publications or papers on the economy of mosques that have been indexed by Dimension and 243 articles for mapping the bibliometrics using R Biblioshiny. The findings indicate that the majority of literature on the mosque economy is published in Human Society Studies. Mosque, Management, and Study are the most often used terms in this research. Additionally, Cardinale MV and Yaacob N authored the most published research. Numerous countries worldwide, including Malaysia, Indonesia, and the United States, have researched the mosque economy. This study discovered that mosques are critical in developing Islamic socio-economic civilization.